2017
DOI: 10.1080/09286586.2017.1339808
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Optic Neuritis in Patients with Different Types of Uveitis

Abstract: Incidence and prevalence of ON among patients with intermediate, posterior and pan uveitis were comparable and higher than the rates in patients with anterior uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Our findings of 10-fold higher odds of previous scleritis among patients with ON compared with controls and 5-fold higher odds of previous uveitis and hazard of incident uveitis are consistent with a US database study (103 867 patients with uveitis, including 974 with ON). This study reported similar ON prevalence in anterior uveitis and the general population (120 per 100 000 population [0.6%]) but higher ON prevalence in intermediate (280 per 100 000 population), posterior (290 per 100 000 population), and panuveitis (380 per 100 000 population).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings of 10-fold higher odds of previous scleritis among patients with ON compared with controls and 5-fold higher odds of previous uveitis and hazard of incident uveitis are consistent with a US database study (103 867 patients with uveitis, including 974 with ON). This study reported similar ON prevalence in anterior uveitis and the general population (120 per 100 000 population [0.6%]) but higher ON prevalence in intermediate (280 per 100 000 population), posterior (290 per 100 000 population), and panuveitis (380 per 100 000 population).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings, of ten-fold higher odds of previous scleritis amongst ON patients than controls, and five-fold higher odds of previous uveitis, and hazard of incident uveitis, are consistent with a USA database study (103,867 uveitis patients, including 974 with ON). 8 This reported similar ON prevalence in anterior uveitis and the general population (0.6%, 120/100,000 people), but higher ON prevalence in intermediate (280/100,000), posterior (290/100,000) and pan-uveitis (380/100,000). MS cohort studies (France n=4300, 33 Turkey n=1702 34 ) similarly report uveitis, especially intermediate and panuveitis, in between 0.52% and 0.65% patients, preceding MS diagnosis in 46%, simultaneous in 18%, and following diagnosis in 36%.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the observed rate is comparable to the background rate reported in patients with uveitis who were not exposed to adalimumab (Guo D, et al, manuscript in progress). 30 Furthermore, there is a known association between anterior and intermediate uveitis and demyelinating disorders 31e33 ; for example, an estimated 7% to 10% of patients with intermediate uveitis also have multiple sclerosis. 34,35 There were no significant changes from baseline for laboratory tests or vital signs (data not shown).…”
Section: Discussionmentioning
confidence: 99%